RITUAL AND REVEAL: THE POWER OF PLOT IN SHIRLEY JACKSON’S "THE LOTTERY" - Mandalahi, Esterlita; Purba, Nurhayati; Siregar, Grace; Siagian, Novitasari (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2025)
ABSTRACT Shirley Jackson’s The Lottery remains one of the most disturbing and widely discussed short stories in American literature. Its enduring appeal lies largely in the carefully crafted plot structure, which cleverly conceals the true nature of the small town’s annual ritual until the story’s climax. This article presents a close reading of the narrative using formalist and structuralist approaches, focusing on how tension and irony are built through narrative delay, symbolic cues, and a cyclical ritual structure. These narrative techniques not only generate emotional tension but also serve as critical tools used by Jackson to challenge themes of social conformity, the banality of evil, and culturally legitimized violence. This study employs a qualitative descriptive method, focusing on literary analysis through close reading and interpretative strategies. The research begins with an intensive reading of The Lottery to identify narrative techniques and literary devices used. This is followed by textual analysis using formalist and structuralist criticism. The study also examines secondary sources from academic journals and literary theory. The final stage involves interpreting meaning to uncover the social, psychological, and ideological implications of the text. By emphasizing the ethical dimension of the plot’s architecture, this study argues that The Lottery goes beyond mere storytelling and functions as a sharp critique of unquestioned traditions, urging readers to confront the hidden violence within normalized communal practices. ABSTRAK The Lottery karya Shirley Jackson tetap menjadi salah satu cerpen yang paling menggelisahkan dan banyak dibahas dalam sastra Amerika. Daya tariknya yang bertahan lama sebagian besar disebabkan oleh struktur plot yang dirancang dengan cermat, yang secara cerdik menyembunyikan sifat sebenarnya dari ritual tahunan di kota kecil tersebut hingga klimaks cerita. Artikel ini menyajikan pembacaan mendalam terhadap narasi menggunakan pendekatan formalis dan strukturalis, dengan fokus pada bagaimana ketegangan dan ironi dibangun melalui penundaan naratif, petunjuk simbolik, serta struktur ritual yang bersifat siklik. Teknik-teknik naratif ini tidak hanya menciptakan ketegangan emosional, tetapi juga berfungsi sebagai alat kritis yang digunakan Jackson untuk menggugat tema konformitas sosial, banalitas kejahatan, dan kekerasan yang dilegitimasi secara budaya. Penelitian ini menggunakan metode deskriptif kualitatif, dengan fokus pada analisis sastra melalui pendekatan close reading dan strategi interpretatif. Penelitian ini diawali dengan pembacaan intensif terhadap cerpen The Lottery untuk mengidentifikasi teknik naratif dan perangkat sastra yang digunakan. Selanjutnya, dilakukan analisis teks dengan pendekatan kritik formalistis dan strukturalis. Peneliti juga mengkaji sumber-sumber sekunder dari jurnal akademik dan teori sastra. Tahapan akhir berupa interpretasi makna untuk mengungkap implikasi sosial, psikologis, dan ideologis dari teks. Dengan menekankan dimensi etis dari arsitektur plot, studi ini berargumen bahwa The Lottery melampaui sekadar penceritaan dan berfungsi sebagai kritik tajam terhadap tradisi yang tidak dipertanyakan, mendorong pembaca untuk menghadapi kekerasan tersembunyi dalam praktik komunal yang telah dinormalisasi.